2017
DOI: 10.1111/jcpt.12499
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel algorithm for detecting glucocorticoid-induced diabetes mellitus using a medical information database

Abstract: Patients with GIDM had significantly higher RIM-HbA1c than patients with non-GIDM. There was a 13% increase in RIM-HbA1c in patients with GIDM compared to the others. Our detection algorithm for GIDM using an MID achieved high sensitivity and specificity, and was superior to one based only on the current JDS DM criteria. Our results suggest that monitoring changes in HbA1c levels is important for detecting GIDM and adds to current diagnostic criteria for type 2 DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…In the present study, we found only one out of 43 patients (2.3%) with glucocorticoid-induced diabetes mellitus. The frequency of glucocorticoid-induced diabetes mellitus in the present study was apparently lower than in a survey in Japan, which reported an incidence of approximately 6%-9% [27].…”
Section: Discussioncontrasting
confidence: 50%
“…In the present study, we found only one out of 43 patients (2.3%) with glucocorticoid-induced diabetes mellitus. The frequency of glucocorticoid-induced diabetes mellitus in the present study was apparently lower than in a survey in Japan, which reported an incidence of approximately 6%-9% [27].…”
Section: Discussioncontrasting
confidence: 50%
“…HbA1c may be a suitable method for diagnosis in patients treated with corticosteroids for >2 months, but it is not useful for patients whose treatment has been initiated more recently. Recently, Japanese scientists developed a detection algorithm for GIDM and suggested that monitoring changes in HbA1c levels is important for detecting GIDM [33]. In patients where HbA1c levels could be unreliable, such as those with hemoglobinopathies, renal failure, or anemia/recent blood transfusion, fructosamine measurements would be a better alternative [5].…”
Section: Definition and Diagnosismentioning
confidence: 99%
“…Growing data in the genomics and metabolomics fields of research provided evidence that occurring of particular SNPs (single nucleotide polymorphisms) and particular amino acids in the baseline plasma metabolite level can be associated with the increased risk for drug-induced diabetes [6]. On the other hand, particular drug classes, e.g., glucocorticosteroids, statins, diuretics and beta-blockers [3, 4] may induce diabetes type 2 more frequently than the other drug classes due to their influence on the hepatic glucose production, pancreatic insulin secretion and peripheral tissues insulin sensitivity [7]. The complex molecular mechanism of drug-induced T2DM varies from one drug class to another (e.g.…”
Section: Introductionmentioning
confidence: 99%